The Creativity of Using Batik Ethnic to Attract Foreign Tourists (Study on Customers of Banyuwangi Batik in Kemiren Village, Glagah District, Banyuwangi Regency, East Java Banyuwangi Regency, East Java) - R. , Adjeng Mariana Febrianti; Widuri Sakti, Intan; Novan Setiawan Nugraha, Deden (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to find out the stretching of using batik that has high creativity and the value of product innovation towards the marketing performance of batik products through customer value. This study uses a snowball sampling method of 200 respondents and is analyzed using the SEM (Structural Equation Modeling) model. The results showed the variable creativity has an influence on customer value by maintaining modern patterns and images, innovation variables have an influence on customer value so that craftsmen can provide maximum value for batik customers, customer value variables have an influence on company performance, creativity variables affect marketing performance through customer value, and innovation variables affect marketing performance through customer value.